A comparative study of clinical, biochemical and hematological profiles in smear positive malaria patients: at a tertiary care center located in rural part of Gujarat, India - Patel, Gaurav I.; Muley, Prasad; Vadher, Abhishek; Suthar, Pokhraj Prakashchandra; Shah, Gautam V.; Patel, Ankitkumar B. (International Journal of Research in Medical Sciences, 2017)
Background: Aims and objectives of current study were to study the clinical, biochemical and hematological profiles in smear positive malaria patients and its correlation to immediate outcome of patient. To analyze the biochemical and hematological imbalances and its correlation with clinical presentation and type of malarial parasites. To elucidate the correlation of hematological and biochemical changes in children infected with malaria and their impact on immediate outcome of patients. Methods:All patients admitted with a diagnosis of malaria in department of Pediatrics at Dhiraj Hospital, Piparia, Vadodara, during the study period of January 2013 to June 2014. Sample size was 106 cases. Inclusion criteria for the study was all children under 18 years of age with smear positive malaria cases diagnosed. The study was done after obtaining a detailed history, complete general physical examination and systemic examination. The patients were subjected to relevant investigations. The data regarding patient particulars, diagnosis and investigations is collected in a specially designed case recording form and transferred to a master chart subjected to statistical methods like mean, standard deviation, proportion, percentage calculation and wherever necessary chi square test for proportion are used. Results: Total 106 patients were enrolled in study. Complications of PF (N=31): Jaundice 16%, severe anemia 23%, thrombocytopenia 29%, leukopenia in 23%, hyponatremia in 29.1%, cerebral malaria in 16% and hyperkalemia in 17%. Complications of PV (N=65): Jaundice 20%, severe anemia 20%, thrombocytopenia 18%, leukopenia in 11%, hyponatremia in 44.6%, hyperkalemia in 9%, cerebral malaria in 12.3% and hypoglycemia in 3.77%. Conclusions:The incidence of malaria is higher in males than females. Thrombocytopenia is very common in malaria, but spontaneous bleeding is not so common finding in malaria. Mixed infections behave like falciparum malaria. P. vivax malaria though traditionally considered to be a benign entity can also have a severe and complicated course, which is usually associated with P. falciparum malaria.